1380 nm VCSELs using surface-activated bonding of GaAs-based DBRs on a Ge substrate - Tomomasa Watanabe; Mikihiro Yokozeki; Masashi Takanohashi; Michinori Shiomi; Hiroshi Nakajima; Masayuki Tanaka; Daiji Kasahara; Noriko Kobayashi; Noriyuki Futagawa (Applied Physics Express)
A wafer-bonded vertical-cavity surface-emitting laser (VCSEL) was demonstrated by surface-activated bonding (SAB) of a GaAs-based distributed Bragg reflector (DBR) on a Ge substrate. Current injection lasing was achieved at the 1380 nm band under continuous-wave operation with AlGaInAs-based multi-quantum wells and a buried tunnel junction for current and optical confinement. The thermal conductivity of the VCSELs bonded by SAB was superior to that of InP VCSELs owing to high heat dissipation of GaAs DBR. This bonding method is suitable for short-wavelength infrared VCSELs and various other applications, including sensing, data communication, and silicon photonics.